Pemasaran Digital sebagai Katalis Perubahan: Inovasi dalam Membangun Ketahanan Pesantren - Rahma Nanda Nur Azizah; Mutiatus Sofiah; Luat happyana (Jurnal Bintang Manajemen, 2024)
This research aims to explore the role of digital marketing as a catalyst for change in building resilience among pesantrens in the digital era. A qualitative method was employed with a case study approach on pesantrens in Banyuwangi that have adopted digital marketing strategies. Data were collected through in-depth interviews with pesantren managers, document analysis, and direct observation of social media content and websites of the pesantrens. Thematic and descriptive analyses were used to understand digital marketing strategies, the impact of content marketing, and the use of social media in building pesantren communities. The findings indicate that effective digital marketing enhances pesantren visibility, community engagement, and student participation in online education programs. Content marketing strategies play a crucial role in conveying Islamic educational values and strengthening pesantren identities, while social media facilitates closer interaction between pesantrens and their communities. These findings provide insights into how pesantrens can strategically leverage digital technology to remain relevant and competitive in the evolving digital era.